Ouabain Counteracts Retinal Ganglion Cell Death Through Modulation of BDNF and IL-1 Signaling Pathways - Amanda Candida da Rocha Oliveira; Camila Saggioro Figueiredo; Ícaro Raony; Juliana Salles Von-Held-Ventura; Marcelo Gomes Granja; Thalita Mázala-de-Oliveira; Vinícius Henrique Pedrosa-Soares; Aline Araujo dos Santos; Elizabeth Giestal-de-Araujo (Brain Sciences)
Background: Ouabain is a steroid hormone that binds to the sodium pump (Na+, K+-ATPase) at physiological (nanomolar) concentrations, activating different signaling pathways. This interaction has been shown to prevent the axotomy-induced death of retinal ganglion cells (RGCs), although the underlying mechanisms remain unclear. Objective: In this study, we investigated potential mechanisms by which ouabain promotes RGC survival using primary cultures of rat neural retina. Results: Our findings indicate that ouabain regulates brain-derived neurotrophic factor (BDNF) signaling in retinal cells via matrix metalloproteinase-9-mediated processing of proBDNF to mature BDNF (mBDNF) and by increasing the phosphorylation of the mBDNF receptor, tropomyosin-related receptor kinase B. Ouabain also enhances the maturation of interleukin (IL)-1β through the increased activation of caspase-1, which mediates the processing of proIL-1β into IL-1β, and transiently upregulates both IL-1 receptor and IL-1 receptor antagonist (IL-1Ra). Treatment using either IL-1β or IL-1Ra alone is sufficient to enhance RGC survival similarly to that achieved with ouabain. Finally, we further show that ouabain prevents RGC death through a complex signaling mechanism shared by BDNF and IL-1β, which includes the activation of the Src and protein kinase C pathways. Conclusions: Collectively, these results suggest that ouabain stimulates the maturation and signaling of both BDNF and IL-1β, which act as key mediators of RGC survival.